2022
DOI: 10.1063/5.0085623
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ga+ milling on the spin waves modes in a Co2MnSi Heusler magnonic crystal

Abstract: Ferromagnetic resonance experiment was performed to study the magnonic modes of an antidot lattice nanopatterned in a sputtered Co2MnSi Heusler alloy thin film. The magnonic crystal was prepared with a Ga+ focused ion beam, and micromagnetic simulations were used to explain qualitatively and quantitatively the complex experimental spin waves spectrum. We demonstrate the necessity to consider the geometrical imperfections and the modification of the Co2MnSi magnetic parameters induced by the nanofabrication pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…In our previous studies, we have shown that multilayer ADLs with perpendicular magnetic anisotropy (PMA) have the potential to be promising patterned systems with periodic magnetization texture to control SW propagation 35 37 . Micromagnetic simulations were used to interpret time-resolved magneto-optical Kerr effect microscopy measurements of SW spectra in ADLs based on [Co/Pd] 8 multilayers 35 .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we have shown that multilayer ADLs with perpendicular magnetic anisotropy (PMA) have the potential to be promising patterned systems with periodic magnetization texture to control SW propagation 35 37 . Micromagnetic simulations were used to interpret time-resolved magneto-optical Kerr effect microscopy measurements of SW spectra in ADLs based on [Co/Pd] 8 multilayers 35 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, ADL based on multilayers with perpendicular magnetic anisotropy (PMA) has been indicated as a patterned system hosting periodic magnetization texture with interesting properties and potential applications. [22,24,18] The results of time-resolved magneto-optical Kerr effect (TR-MOKE) microscopy measurements of SW excitations in ADL based on [Co/Pd] 8 multilayers were interpreted with micromagnetic simulations. [22] To explain low frequency mode in the spectra, the authors assumed that around the holes there is a rim with modified magnetic properties formed during the patterning process, i.e., Ga ions used in focused ion beam (FIB) in the patterning process penetrate larger area than the antidots.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, I. Abdallah et al explored the effects of 150 keV He + irradiation on 40 nm Co2MnSi thin films as a substitute for annealing to induce B2 order, noting a reduction in magnetization with increasing fluence, and later, they reported structural effects as well [193]- [195]. Further relevant studies are cited in references [196]- [199].…”
Section: Modification In Ferromagnetic Thin Films and Multilayer Stacksmentioning
confidence: 99%